Level-IV-Cavathrombus: eine seltene Diagnose bei Patienten mit Nierenzellkarzinom - Hofer, Luisa; Gasch, Claudia; Hatiboglu, Gencay; Motsch, Johann; Grüllich, Carsten; Duensing, Stefan; Hohenfellner, Markus (Der Urologe, 2017)
Renal cell carcinoma in combination with a supradiaphragmatic tumor thrombus is a rare tumor entity. Radical surgery including nephrectomy and thrombectomy is still considered standard treatment. The extent of the tumor thrombus should be preoperatively evaluated by MRI and TEE. An interdisciplinary team is important for surgery planning and realization. Despite the known risks of an operation, a longer overall survival is achieved.